PENGARUH LINGKUNGAN SOSIAL TERHADAP HASIL BELAJAR SISWA KELAS III SD - Juliana Manurung; Antonius Remigius Abi; Reflina Sinaga; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines the effect of the social environment on students’ learning outcomes at the third-grade level of SD Negeri 038095 Barisan Sirait Siempat Nempu Hilir Dairi in the academic year 2021/2022. The research in this article used the descriptive-analytic method. The research population involved 31 third-grade students of SD Negeri 038095 Barisan Sirait Siempat Nempu Hilir in Dairi. The sampling technique used purposive samples. The results indicated that the correlation test can be seen in the correlation coefficient value of 0.991, which means rcount (0.991) > rtable (0.355), thus, Ha was accepted. Hence, there was a very strong influence between the social environment and the learning outcomes of the third-grade students at SD Negeri 038095 Barisan Sirait Siempat Nempu Hilir in Dairi. It can also be seen from the results of the t-test where tcount 40.768 > ttable 2.045, thus, Ha was accepted. It shows that the social environment has a significant influence on students’ learning outcomes for class III at SD Negeri 038095 Barisan Sirait Siempat Nempu Hilir in Dairi in the academic year 2021/2022.